ASUS Cusi Series: SiS VGA Driver for MS/Other OS, 3D Audio Driver for Windows OS, ASUS PC Probe - ASUS..... (ASUSTEK Computer, 2001)
Program; Isi: Acrobat, AFLASH, Asusupdt, Audio, Cyberlink, Display, Hotkey, IDE, LAN, Modem, pCCLIN, PDVD, Probe, PWPlayer, dll; Judul dalam kemasan.